A study on the growth of red mangrove (Rhizophora mangle L.) in Cape Coral, Florida, US (Flora Marina, 2022)
An analysis of shoot extension growth of Rhizophora mangle is presented, based on the continuous observation of a small population over a period of two years in Cape Coral, Florida, United States.